Computational model of a 3D dosimetry system - ArcCHECK® (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Ionizing radiation therapies have been improving over the years, becoming more specific for each patient. Thereby, as the treatment planning system (TPS) complexities increases, the quality assurance (QA) methods have to be in constant evolution. One of the techniques that demand great complexity is the Volumetric Modulated Arc Therapy (VMAT), and one possible way to VMAT commissioning is using 3D dosimetry systems. Recently a new 3D dosimetry system called ArcCHECK had been developed and commercialized mainly for VMAT quality assurance. It is water-equivalent and composed by an array of 1386 diodes arranged in a helical pattern. Since simulation methods, like Monte Carlo method, ensure highly accurate results, MCNP (A General Monte Carlo N-Particle Transport Code System) is totally reliable for problems that involve radiation transport. This work presents two computational models for Monte Carlo simulations to predict detection responses in the QA procedure using the ArcCHECK. The computational models were validated comparing the system responses obtained from MCNP6 simulations against measured responses due to a 6 MeV clinical photon beam from a Linear Accelerator. 2D dose maps were reported here with good agreement between simulated and measured values.